Digitalisasi Media Pembelajaran sebagai Strategi Penguatan Komunikasi Budaya dan Keterampilan Komunikasi Peserta Didik - Suparyadi, Suparyadi; Rafi'i, Rafi'i; Ningsih, Titiek Surya; Irawan, Novida; Sumirat, Pepen (Jurnal Pendidikan Indonesia : Teori, Penelitian, dan Inovasi, 2025)
The digitalization of learning media has become a key strategy to enhance students’ communication skills and cultural awareness in 21st-century education. This study aims to examine the use of digital media as a tool to strengthen cultural communication and student communication competence in multicultural classroom settings. Using a descriptive qualitative approach, data were collected through observation, interviews, and documentation at SMA Waskito, South Tangerang. Ting-Toomey and Dorjee’s (2018) intercultural communication theory was applied to analyze how students effectively convey messages across cultural differences. The results show that digital media such as videos, infographics, and online platforms encouraged students to participate actively and express their cultural identities more confidently. Teachers acted as collaborative facilitators who created space for intercultural dialogue. Although challenges such as limited access and unequal digital literacy were present, adaptive teaching strategies helped ensure inclusive and meaningful learning. Therefore, digital media serves not only as a learning aid but also as a strategic tool to foster students’ intercultural communication competence.ABSTRAKDigitalisasi media pembelajaran menjadi strategi kunci dalam meningkatkan keterampilan komunikasi dan kesadaran budaya peserta didik di era pendidikan abad ke-21. Penelitian ini bertujuan untuk mengkaji pemanfaatan media digital sebagai sarana penguatan komunikasi budaya dan kemampuan komunikasi siswa dalam konteks multikultural. Menggunakan pendekatan kualitatif deskriptif, data dikumpulkan melalui observasi, wawancara, dan dokumentasi di SMA Waskito, Tangerang Selatan. Teori komunikasi lintas budaya Ting-Toomey dan Dorjee (2018) digunakan sebagai kerangka analisis untuk memahami cara siswa menyampaikan pesan secara efektif dalam keberagaman. Hasil penelitian menunjukkan bahwa media digital seperti video, infografik, dan platform daring mendorong partisipasi aktif siswa serta memperkuat ekspresi identitas budaya lokal. Guru berperan sebagai fasilitator kolaboratif dalam menciptakan ruang dialog antarbudaya. Meskipun terdapat tantangan teknis dan literasi digital yang belum merata, strategi adaptif guru mampu menjaga proses pembelajaran tetap inklusif dan bermakna. Dengan demikian, digitalisasi media tidak hanya mendukung pembelajaran, tetapi juga membentuk keterampilan komunikasi lintas budaya siswa.